Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

a) (x + 7)(2x - 1)
b) (3x + 4)(x - 5)
c) (y + 9) (y + 4)
d) (b - 12)(b - 3)
please solve these i’m begging


Sagot :

A) 2x to the power of 2 +13x-7
B) 3x to the power of 2 -11x -20
C) y to the power of 2 + 13y+36
D) b to the power of 2 -15b + 36

Answer:

A.) [tex]2x^2 + 13x - 7[/tex]

B.) [tex]3x^2 - 11x - 20[/tex]

C.) [tex]y^2 + 13y + 36[/tex]

D.) [tex]b^2 - 15b + 36[/tex]

Step-by-step explanation:

For all of these you want to multiply the first thingy (Ex. x) in the first parenthesis by the first in the second parenthesis (Ex. 2x) plus the first one in the first (Ex. x) times the second one in the second (Ex. -1) plus the second one in the first one (Ex. 7) times the first one in the second parenthesis (Ex. 2x)  plus the second one in the first parenthesis (Ex. 7) times the second one in the second (Ex. -1)

A.) (x + 7)(2x - 1) = (2x * x) + (-1 * x) + (7 * 2x) + (7 * -1) = 2x^2 -x + 14x - 7 = 2x^2 + 13x - 7

B.) (3x + 4)(x - 5) = (3x * x) + (3x * -5) + (4 * x) + (4 * -5) = 3x^2 - 15x + 4x - 20 = 3x^2 - 11x - 20

C.) (y + 9) (y + 4) = (y * y) + (4 * y) + (9 * y) + (9 * 4) = y^2 + 4y + 9y + 36 = y^2 + 13y + 36

D.) (b - 12)(b - 3) = (b * b) + (b * -3) + (-12 * b) + (-12 * -3) = b^2 - 3b - 12b + 36 = b^2 - 15b + 36